The Effect of HIV-Centered Obstetric Care on Perinatal Outcomes Among a Cohort of Women Living With HIV. (1st August 2017) - Powell, Anna M.; DeVita, Julia M.; Ogburu-Ogbonnaya, Amartha; Peterson, Andrea; Lazenby, Gweneth B.
Abstract : Background: Elimination of perinatal transmission is possible but limited by missed care opportunities. Our objective was to investigate the effects of HIV-centered obstetric care (HCC) on missed care opportunities and perinatal HIV transmission in 2 obstetric cohorts at our institution from 2000 to 2014. Methods: This was a retrospective cohort study of HIV-exposed mother–infant pairs delivering from 2000 to 2014, analyzed according to SQUIRE 2.0 (Standards for Quality Improvement Reporting Excellence) guidelines. Before 2009, women received care in high-risk obstetric care (HRC); subsequently, an HCC service was established. Women who received HRC vs HCC obstetric care were compared to determine differences in maternal and neonatal outcomes. Continuous variables were compared with Student t test and Wilcoxon rank sum tests. Categorical variables were compared using χ 2 test and Fisher exact test. Logistic regression analyses were performed to determine factors associated with outcomes of interest. Results: Over 14 years, 161 women delivered 217 HIV-exposed infants; 78 (36%) women received HCC. Two perinatal HIV transmissions (1.5%) occurred in HRC group compared with none in the HCC group ( P = 0.3). Women in HCC were more likely to have HIV RNA viral load <1000 copies per milliliter at delivery (12% vs 26%, P = 0.02), have a contraception plan before delivery (93% vs 60%, P < 0.001), return for postpartum evaluation (80% vs 63%, P = 0.01), and have undetectable HIV viral load postpartum (50 copies per milliliter vs 2067, P < 0.0001). Conclusions: HCC can potentially reduce the risk of perinatal HIV transmission by improving maternal virologic control during pregnancy and postpartum and increasing postpartum contraceptive use. Abstract : HIV-centered obstetric care may decrease missed care opportunities and risk factors for perinatal HIV transmission, increase uptake of long acting reversible contraception postpartum, and increase retention in postpartum obstetric and HIV care.